Curtailment of Nephrotoxicity of Polyethylene Glycol via Moringa Oleifera Leaf Extract in Male Rats (Journal of Pharmaceutical Negative Results, 2022)
Polyethylene glycols (PEG) are water-soluble chemicals composed of periodic ethylene glycol units, mostly used in industry and medicine. They have several chemical and physical features, which may lead to possible toxicity. Moringa oleifera is used as an antioxidant because of its ability to inhibition of protein denaturation and scavenge free radicals. Previous studies do not report enough data on the nephrotoxicity of polyethylene glycol and the protective role of Moringa oleifera leaf extract (MOLE). So, the current study was conducted to address this affair. Male rats were split for six set (six each group) (group 1, as control; group 2, MOLE; group 3, PEG 50 mg/kg; group 4, MOLE + PEG 50 mg/kg; group 5, PEG 100 mg/kg; group 6, MOLE + PEG 100 mg/kg). Rats were administered orally daily for 45 days. The obtained results showed that treatment with both doses of PEG caused a significant increase in IL- 6, TNF-α, NOx, TBARS, uric acid, and GST comparison to group 1. While, both doses of PEG significantly suppressed expression of PGC-1α, levels of p53, GR, GPx and GSH declined compared to group 1. The co-complementary with MOLE leads to safeguarding the kidney from the toxicity induced by PEG at all levels.